(untitled) (Critical Journal of Social Sciences, 2026)
This article investigates the presence of the demographic implosion phenomenon in Cuba by explaining the downward movement of its population during the period between 2016 and 2024, with an emphasis on the period following the health collapse caused by the spread of the coronavirus (SARS-CoV-2). This proposal uses the estimation of balance rates or the net behavior of vital events (natural or migratory) as components of the compensating equation or demographic balance, to contrast the factors behind this population decline. The results are shocking when verifying the precipitous drop in the number of inhabitants starting in 2021 due to the increase in deaths and, mainly, due to the immediate acceleration of migration. This is accompanied by a marked deterioration in its socioeconomic background and allows us to assert the occurrence of a severe implosion process regarding the inhabitants of its society.